3D Ultrasound Measurements Are Highly Sensitive to Monitor Formation and Progression of Abdominal Aortic Aneurysms in Mouse Models - Ibrahim, Nahla; Bleichert, Sonja; Klopf, Johannes; Kurzreiter, Gabriel; Knöbl, Viktoria; Hayden, Hubert; Busch, Albert; Stiglbauer-Tscholakoff, Alexander; Eilenberg, Wolf; Neumayer, Christoph; Bailey, Marc A.; Brostjan, Christine (Frontiers in Cardiovascular Medicine, 2022)
Background: Available mouse models for abdominal aortic aneurysms (AAAs) differ substantially in the applied triggers, associated pathomechanisms and rate of vessel expansion. While maximum aortic diameter (determined after aneurysm excision or by 2D ultrasound) is commonly applied to document aneurysm development, we evaluated the sensitivity and reproducibility of 3D ultrasound to monitor aneurysm growth in four distinct mouse models of AAA. Methods: The models included angiotensin-II infusion in ApoE deficient mice, topical elastase application on aortas in C57BL/6J mice (with or without oral administration of β-aminoproprionitrile) and intraluminal elastase perfusion in C57BL/6J mice. AAA development was monitored using semi-automated 3D ultrasound for aortic volume calculation over 12 mm length and assessment of maximum aortic diameter. Results: While the models differed substantially in the time course of aneurysm development, 3D ultrasound measurements (volume and diameter) proved highly reproducible with concordance correlation coefficients >0.93 and variations below 9% between two independent observers. Except for the elastase perfusion model where aorta expansion was lowest and best detected by diameter increase, all other models showed high sensitivity of absolute volume and diameter measurements in monitoring AAA formation and progression by 3D ultrasound. When compared to standard 2D ultrasound, the 3D derived parameters generally reached the highest effect size. Conclusion: This study has yielded novel information on the robustness and limitations of semi-automated 3D ultrasound analysis and provided the first direct comparison of aortic volume increase over time in four widely applied mouse models of AAA. While 3D ultrasound generally proved highly sensitive in detecting early AAA formation, the 3D based volume analysis was found inferior to maximum diameter assessment in the elastase perfusion model where the extent of inflicted local injury is determined by individual anatomical features.